Research on sustainable cycle of new sustainable development energy economy - Bao, Junsong (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of the sharing economy on achieving the Sustainable Development Goals (SDGs) within China's manufacturing sector. It focuses on how energy efficiency, resource optimization, and cost savings contribute to SDG success, with an emphasis on the mediating role of energy efficiency. Primary data were gathered through surveys of managers from various manufacturing firms in China, representing different industrial sectors to provide a comprehensive understanding. The study used Smart-PLS (Partial Least Squares Structural Equation Modeling) to analyze the relationships between energy efficiency improvements, resource utilization, cost reductions, and SDG outcomes. The results show that efficient energy use, energy efficiency improvements, and cost savings positively affect SDG achievement in manufacturing. Notably, energy efficiency improvements serve as a key intermediary connecting the sharing economy’s benefits to SDG success. The study concludes that the sharing economy significantly contributes to sustainable development in the manufacturing sector, with energy efficiency playing a crucial role in achieving SDGs. This research offers actionable insights for policymakers, industry leaders, and regulators, recommending the integration of sharing economy models to optimize resource use and foster sustainability.